DIDACTIC REQUIREMENTS AND METHODS FOR DEVELOPING THE ARTISTIC-AESTHETIC TASTE OF PRIMARY CLASS STUDENTS THROUGH MUSIC (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article describes didactic requirements and interactive methods for developing the artistic and aesthetic taste of elementary school students through music.